EvoDevo - BioMed Central Ltd. (London : BioMed Central, 2010)
"EvoDevo publishes articles on a broad range of topics associated with the translation of genotype to phenotype in a phylogenetic context. Understanding the history of life, the evolution of novelty and the generation of form, whether through embryogenesis, budding, or regeneration are amongst the greatest challenges in biology. We support the understanding of these processes through the many complementary approaches that characterize the field of evo-devo."
Mode of access: World Wide Web.
Description based on first issue; title from homepage (viewed Aug. 12, 2010).
Latest issue consulted: Volume 8 (2017) (BioMed Central, viewed October 13, 2017).
Keywords: Evolution (Biology) -- Periodicals; Developmental biology -- Periodicals; Developmental biology; Evolution (Biology); Biological Evolution; Developmental Biology; Evolution; Electronic journals